Design of Fe-containing GdTbCoAl high-entropy-metallic-glass composite microwires with tunable Curie temperatures and enhanced cooling efficiency. (August 2021) - Yin, Hangboce; Law, Jiayan; Huang, Yongjiang; Franco, Victorino; Shen, Hongxian; Jiang, Sida; Bao, Ying; Sun, Jianfei
Graphical abstract: Highlights: Nanocrystalline Fe-containing GdTbCoAl high-entropy-metallic-glass were attained. Curie temperature is tuned by Fe-doping in a wide temperature range of 81–108 K. Magnetic entropy change 7.6–8.9 J kg −1 K −1 for 5 T were achieved. The dual-phase structure with T C distribution enhances the cooling efficiency. Abstract: Through designing the composition and processing approach, the non-equiatomic (Gd36 Tb20 Co20 Al24 )100-x Fex (x = 0, 1, 2 and 3 at.%) high-entropy-metallic-glass (HE-MG) alloy microwires were successfully fabricated by melt-extraction technique. The microstructure and magnetocaloric properties of the microwires were systematically investigated. The microwires possess tunable Curie temperatures, i.e. 81–108 K, above the typical rare-earth (RE) containing HE-MG reports. The high Curie temperatures are attributed to the designed composition. Magnetocaloric response peak values of Fe-containing GdTbCoAl alloy microwires range 7.6–8.9 J kg −1 K −1 (5 T), which are comparable to those of many outstanding RE-containing magnetocaloric HE-MGs. The characteristics of the melt-extraction method, combining with compositional effects, favor the formation of amorphous and nanocrystalline phases. The increase in the cooling efficiency for microwires with higher Fe content can be attributed to the broadening of the Curie temperature distribution induced by the composition difference between nanocrystalline phase and amorphous matrix. The designed composition and the melt-extraction processing approach for Fe-containing GdTbCoAl alloys can tune their Curie temperatures towards a temperature range of natural gas liquefaction and improve their magnetocaloric properties. This demonstrates that Fe-containing GdTbCoAl HE-MG composite microwires have great potential as high-performance magnetic refrigerants.